Causes of Undergraduate Students' Underachievement in a Gulf Cooperation Council Country (GCC) University. (September 2022) - Johnson, Chithira; Gitay, Rizwan; Al Hazaa, Khalifa; Abdel-Salam, Abdel-Salam G.; Mohamed, Radwa Ismail; BenSaid, Ahmed; Al-Tameemi, Rusol Adil Naji; Romanowski, Michael H.
UNESCO reports enrollment in higher education in the Arab and Gulf Cooperation Council region doubled from 5.1 million in 2000 to 10.7 million in 2015. Despite significant budgets and the world's lowest teacher-to-student ratio, higher education in this region is plagued by student underachievement. This study identifies academic underachievement factors among undergraduate students at risk at a national university in the GCC. As part of the Intrusive Intervention Program, students were required to complete an Academic Success Plan that delineated academic, personal, social, career, and other academic underachievement reasons. Based on 5, 040 students' responses that indicated their academic underachievement causes, findings reported that students perceived academic factors as the most recurrent reason for academic underachievement. In contrast, social adjustment causes were found to be the least recurrent. Specific causes are reported under each category and discussion is provided against gender, nationality, major, and classification.